Evaluación de diferentes niveles de orégano (origanum vulgare) en pollos de engorde. - Tubón Quinfia, Franklin Estalin (2020)
The following investigation was carried out in the community La Estancia, San Fernando parish of Ambato canton, province of Tungurahua; we analyze the effect of different levels of oregano (Origanum vulgare) as a growth promoter in broilers, compared to a treatment and its influence on zootechnical, parameter productive and economic for 8 weeks. 100 broiler chickens were used divided into five treatments (TT = 0g, T1 = 25g, T2 = 50g, T3 = 75g and T4 = 100g) with 5 repetitions each and a U.E size of 4; The design of the experiment was DCA. We began the reception with weighing and feeding of the newborn chickens, and the differentiated supply of oregano infused in the drinking water because of 25, 50, 75 and 1 ’grams per liter of water; food supply and waste weighing were daily and bird weight registration was performed every 5 days during the 55-day field trial. In conclusion, we state that the bromatological analysis of the fresh product evidently determined that its protein-energy intake is minimal, the chickens had an average initial weight of 40.7 grams. We performed the ADEVA and concluded that the best results in weight (P) and feed intake (CoAl) until the 25th day of the trial, were obtained by the chickens that were supplied with the infusion of oregano in the drinking water at a rate of 100g / lt of water with a statistical significance of P <0.05; from day 30 to day 55, the weights showed there is no statistical differences. On the other hand, indicators of weight gain (GP), food conversion (CA), food efficiency index (IEA) did not report statistical differences between treatments from day 1 and during the 55 days of study; considering that their values are within the recommended parameters for the conditions and altitude floor of the area. Regarding the cost per kilogram of weight gain ($ / kg of GP) of the bird, no statistical differences were obtained at all stages (5, 10, 15, 20, 25, 30, 35, 40, 45.50 and 55 days) The economic benefit / cost analysis (B / C) was favorable for the control treatment (TT) with 1.25 of B / C that is normal if we consider that in the other treatments we use an additional input as a result the higher B / C It is from treatment 4 with 100 grams of oregano per liter of drinking water with 1.15 B / C.